Front Cover: A Two‐Week Treatment with Plant Extracts Changes Gut Microbiota, Caecum Metabolome, and Markers of Lipid Metabolism in ob/ob Mice. Issue 17 (12th September 2019) - Brochot, Amandine; Azalbert, Vincent; Landrier, Jean‐François; Tourniaire, Franck; Serino, Matteo
Abstract : Mol. Nutr. Food Res . 2019, 63, 1900403 DOI: 10.1002/mnfr.201900403 In article number 1900403, Matteo Serino and co‐workers find that in ob/ob mice, a two week treatment with plant extracts affects gut microbiota, caecum metabolome, markers of plasma lipid metabolism, as well as white adipose tissue and liver gene expression. These findings are depending on both the nature and dose of the tested extract.